Case Report: Single-port laparoscopic total gastrectomy for gastric cancer in patient with situs inversus totalis - Lee, In Young; Lee, Danbi; Lee, Chang Min (Frontiers in Oncology, 2023)
Situs inversus totalis (SIT) is a rare anatomical condition, where all the viscera appear in its reverse position. Although minimally invasive surgery has evolved to achieve totally laparoscopic gastrectomy for gastric cancer patients with SIT, it is difficult to perform lymphadenectomy in such a transposed anatomical condition. Recently, we performed a single-port laparoscopic total gastrectomy (SPTG) for gastric cancer in a patient with SIT. No postoperative complications or dietary problems were observed. Based on this experience, we are to design a safe strategy to perform D2 lymphadenectomy during SPTG in patients with SIT.